PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN TOLAK ANGIN KEMASAN SACHET (STUDI KASUS DI APOTEK X DENPASAR SELATAN) - Listiani, Putu Ayu Ratih; Gusti Ayu Oviani; Ketut Soma Asih (Institut Teknologi dan Kesehatan Bintang Persada, 2024)
Tolak Angin is a traditional medicine in liquid form produced by PT Jamu Sido Muncul. Increasing competition for traditional medicines demands efforts to improve brand image and product quality. These two factors determine the decision to purchase Tolak Angin. The purpose of this research was to determine the influence of Brand Image and Product Quality on Purchasing Decisions. The data collection method used in this research was observation with a cross sectional design and using total sampling techniques. The sample in this study consisted of 43 respondents who met the inclusion criteria and did not meet the exclusion criteria. The results of this study show that data on the characteristics of the largest number of respondents aged 26-36 years reached 48.8% (21 respondents), private employee work was 34.9% (15 (respondents), gender was 60.5% (26 respondents), last education reached 60.5% (26 respondents), monthly income > Rp. 2,500,000- Rp. 3,500,000 and > Rp. 3,500,000 was 30.2% (13 respondents), length of visit 2- 3x was 30, 2% (13 respondents), duration of use < 1 year as much as 37.2% (16 respondents). Brand Image influences purchasing decisions giving a Sig value (0.002 < 0.005), Product Quality influences purchasing decisions giving a Sig value (0.002 < 0.005) and Brand Image and Product Quality simultaneously influence purchasing decisions giving a Sig value (0.000 < 0.005). This means that the better the Brand Image and product quality, the higher the consumer's tendency to buy Tolak Angin Sachet Packaging.